Relationship-Specific Investments and Intellectual Property Rights Enforcement with Heterogeneous Suppliers - Alireza Naghavi; Shin-Kun Peng; Yingyi Tsai (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
This paper examines the impact of intellectual property rights (IPR) enforcement on multinationals' choice of input suppliers and industry profits in a host economy. The framework consists of suppliers with heterogeneous capabilities who must engage in a relation-specific investment to customize intermediate inputs upon a transfer payment by final producers. An outsourcing contract with better technologically-endowed suppliers requires a lower transfer and generates a higher surplus. Stronger IPR enforcement leads firms to self-select into better quality suppliers on average by reducing their outside option. Weak legal institutions instead make it possible for a larger range of suppliers, including the less capable ones, to form partnerships by granting them a larger outside option. A better IPR environment is more likely to harm lagging countries where the technology distribution is characterized by less capable suppliers.
Keywords: O34; L24; F21; F23; O32; L22; D23; 330